Common susceptibility alleles and SQSTM1 mutations predict disease extent and severity in a multinational study of patients with Paget's disease. (18th October 2013) - Albagha, Omar ME; Visconti, Micaela Rios; Alonso, Nerea; Wani, Sachin; Goodman, Kirsteen; Fraser, William D; Gennari, Luigi; Merlotti, Daniela; Gianfrancesco, Fernando; Esposito, Teresa; Rendina, Domenico; di Stefano, Marco; et al.
ABSTRACT Paget's disease of bone (PDB) has a strong genetic component. Here, we investigated possible associations between genetic variants that predispose to PDB and disease severity. Allelic variants identified as predictors of PDB from genome‐wide association studies were analyzed in 1940 PDB patients from the United Kingdom, Italy, Western Australia, and Spain. A cumulative risk allele score was constructed by adding the variants together and relating this to markers of disease severity, alone and in combination with SQSTM1 mutations. In SQSTM1‐negative patients, risk allele scores in the highest tertile were associated with a 27% increase in disease extent compared with the lowest tertile (p < 0.00001) with intermediate values in the middle tertile (20% increase; p = 0.0007). The effects were similar for disease severity score, which was 15% (p = 0.01) and 25% (p < 0.00001) higher in the middle and upper tertiles, respectively. Risk allele score remained a significant predictor of extent and severity when SQSTM‐positive individuals were included, with an effect size approximately one‐third of that observed with SQSTM1 mutations. A genetic risk score was developed by combining information from both markers, which identified subgroups of individuals with low, medium, and high levels of severity with a specificity of 70% and sensitivity of 55%. Risk allele scores and SQSTM1 mutations both predict extent and severity of PDB. It is possible that with further refinement, genetic profiling may be of clinical value in identifying individuals at high risk of severe disease who might benefit from enhanced surveillance and early intervention. © 2013 American Society for Bone and Mineral Research